Up-to-Date Overview of the Use of Natural Ingredients in Sunscreens - Resende, Diana I. S. P. (2022)
The photoprotective skincare segment is in high demand to meet consumer concerns on UV-induced skin damage, with a recent trend towards sunscreen alternatives with a natural origin. In this study, the use of natural ingredients, either from terrestrial or marine origin, in a panel of 444 sunscreen commercial formulations (2021) was analyzed. Ingredients from terrestrial organisms represent the large majority found in the analyzed sunscreen formulations (48%), whereas marine ingredients are present only in 13% of the analyzed products. A deeper analysis regarding the most prevalent families of ingredients from terrestrial and marine organisms used as top ingredients is also presented, as well as their mechanisms of action. This study provides an up-to-date overview of the sunscreen market regarding the use of natural ingredients, which is of relevance for scientists involved in the development of new sunscreens to identify opportunities for innovation.